Statistical Inference for Stochastic Differential Equations with Small Noises - Liang Shen; Qingsong Xu (Abstract and Applied Analysis)
This paper proposes the least squares method to estimate the drift parameter for the stochastic differential equations driven by small noises, which is more general than pure jump α-stable noises. The asymptotic property of this least squares estimator is studied under some regularity conditions. The asymptotic distribution of the estimator is shown to be the convolution of a stable distribution and a normal distribution, which is completely different from the classical cases.